The direction and development of pop music in Malaysia. A case study in Faculty of Music UiTM / Wan Harris Budiman Abdul Khalid - Abdul Khalid, Wan Harris Budiman (Faculty of Music, 2012)
This study was carried out in September 2011 - January 2012 in the Faculty of Music. Universiti Teknologi MARA, Shah Alam. The scope of study focused on Malaysian composers, who teach composition in Faculty of Music and also music students from Diploma and Degree program. This study was initiated based on the pop music direction and development in Malaysia. The main objectives of this study were: 1) to study on pop music acceptance among music students, 2) to investigate on factors that influence on pop music development in Malaysia, 3) to determined ways to improve pop music as to become more develop in the future. Survey questionnaires were distributed directly to the music students in various places in university followed by interview on selective respondents in the faculty. Analysis was done using the SPSS VC12.0 making use of descriptive data, percentages and men scores. Findings showed that pop music was well accepted by music lovers as it is simple, one of the music types that often heard in our daily life, most general listeners were not exposed to any other music type and they have their awareness towards the direction of pop music in the world. Next findings also show that good and well music arrangement become the best factors to develop pop music in Malaysia. Therefore, it is highly necessary for our country to have as many as talented and educated composers and arrangers in order to help improve the quality of pop music as well as develop music industry healthily. Besides that, there are many proactive ways to improve pop music as to become more develop in the future mainly; high music knowledge, creative and explorative among music practitioners, well form and structure, additional support and SWOT Analysis. Additionally, these were suggested as to help our country, Malaysia, to improve the quality of pop music, popularized singers, musicians and composers as well as to enhance and exalt the music industry to achieve the world global level and standard.